Academic Motivation Among Nusa Cendana University Students - Harnita Erwanda Widyanti Djawa; Mariana Dinah Ch, Lerik; Shela Christine Pello (Sean Institute, 2026)
Academic motivation is an internal and external drive that influences students' academic efforts and achievements, so it is important to measure it from the beginning of the lecture because it is closely related to learning engagement and academic success. Early monitoring of academic motivation allows higher education institutions to provide appropriate support for students who are at risk of experiencing a decline in motivation. This study aims to analyze the academic motivation of Nusa Cendana University students in the 2024 academic year. This study uses a descriptive quantitative approach with 361 active Nusa Cendana University students as respondents, consisting of 147 male students and 214 female students. Respondents were selected using purposive sampling, with respondents divided by study program using proportionate stratified sampling. Data collection was conducted through questionnaires. The results showed that the academic motivation of Nusa Cendana University students was generally in the moderate category. Moderate academic motivation was most commonly found in 19-year-old students, as well as in male and female students without any significant differences. Variations in academic motivation were found between faculties and study programs, with FAPERTA having the highest proportion of moderate motivation, FISIP showing a prominent proportion of low motivation, and FEB being dominated by high motivation. In terms of motivation, extrinsic motivation was the most dominant aspect, indicating that students' academic motivation was more influenced by external factors. The results of this study are expected to be taken into consideration by institutions in designing academic policies and programs that support the improvement of intrinsic motivation, as well as a reference for further research with more diverse approaches and variables.